FungalBraid 2.0: expanding the synthetic biology toolbox for the biotechnological exploitation of filamentous fungi - Moreno-Giménez, Elena; Gandía, Mónica; Sáez, Zara; Manzanares, Paloma; Yenush, Lynne; Orzáez, Diego; Marcos, Jose F.; Garrigues, Sandra (Frontiers in Bioengineering and Biotechnology, 2023)
Fungal synthetic biology is a rapidly expanding field that aims to optimize the biotechnological exploitation of fungi through the generation of standard, ready-to-use genetic elements, and universal syntax and rules for contributory use by the fungal research community. Recently, an increasing number of synthetic biology toolkits have been developed and applied to filamentous fungi, which highlights the relevance of these organisms in the biotechnology field. The FungalBraid (FB) modular cloning platform enables interchangeability of DNA parts with the GoldenBraid (GB) platform, which is designed for plants, and other systems that are compatible with the standard Golden Gate cloning and syntax, and uses binary pCAMBIA-derived vectors to allow Agrobacterium tumefaciens-mediated transformation of a wide range of fungal species. In this study, we have expanded the original FB catalog by adding 27 new DNA parts that were functionally validated in vivo. Among these are the resistance selection markers for the antibiotics phleomycin and terbinafine, as well as the uridine-auxotrophic marker pyr4. We also used a normalized luciferase reporter system to validate several promoters, such as PpkiA, P7760, Pef1α, and PafpB constitutive promoters, and PglaA, PamyB, and PxlnA inducible promoters. Additionally, the recently developed dCas9-regulated GB_SynP synthetic promoter collection for orthogonal CRISPR activation (CRISPRa) in plants has been adapted in fungi through the FB system. In general, the expansion of the FB catalog is of great interest to the scientific community since it increases the number of possible modular and interchangeable DNA assemblies, exponentially increasing the possibilities of studying, developing, and exploiting filamentous fungi.